Efektivitas Komunikasi dalam Pembelajaran Berbasis E-learning di Universitas Islam Bandung - Dennis Lumahing Wijaya; Anne Maryani (Bandung Conference Series: Communication Management, 2023)
Abstract. More and more, technological developments continue to progress rapidly, especially in this era of communication. It is proven by the presence of the internet, digitization, artificial intelligence, machine learning, big data, and others. Coupled with the Covid-19 pandemic which caused a change in the learning mechanism, which was originally face-to-face, it changed by utilizing the internet network into distance learning, this was also implemented by the Islamic University of Bandung by transforming face-to-face learning into using an e-learning website. However, in practice, e-learning-based learning is found to have several obstacles such as lack of understanding of the material, lack of interaction between users, and others. Therefore, this study aims to determine the effectiveness of communication that occurs during e-learning-based learning at the Islamic University of Bandung. The method used in this research is descriptive-quantitative with data collection techniques using questionnaires and literature study. The population of this study were students of Faculty of Communication at the Islamic University of Bandung with a total of 368 people. This study also uses a simple random sampling technique in the process of determining the sample, so that the calculation results determine that the sample is 79 people. The results of this study are the effectiveness of communication in e-learning-based learning at the Islamic University of Bandung is quite good, this is because e-learning at the Islamic University of Bandung has applied aspects of Credibility, Context, Content, Clarity, Continuity and Consistency, Capability of Audience, and Channels of Distribution and make maximum use of it. Abstrak. Kian hari, perkembangan teknologi terus mengalami kemajuan pesat, terlebih pada era komunikasi seperti sekarang ini. Terbukti dengan hadirnya internet, digitalisasi, artificial intelegent, machine learning, big data, dan lain-lain. Ditambah dengan adanya pandemi Covid-19 yang menyebabkan perubahan mekanisme pembelajaran yang pada awalnya tatap muka berubah dengan memanfaatkan jaringan internet menjadi pembelajaran jarak jauh, hal ini pun diterapkan oleh Universitas Islam Bandung dengan mentransformasi pembelajaran tatap muka menjadi menggunakan website e-learning. Akan tetapi dalam praktiknya pembelajaran berbasis e-learning ditemukan beberapa hambatan seperti kurangnya pemahaman materi, kurangnya interaksi antar pengguna, dan lain-lain. Maka dari itu penelitian ini bertujuan untuk mengetahui efektivitas komunikasi yang terjadi saat pembelajaran berbasis e-learning di Universitas Islam Bandung. Metode yang digunakan pada penelitian ini adalah deskriptif-kuantitatif dengan teknik pengumpulan data menggunakan kuisioner dan studi kepustakaan. Populasi dari penelitian ini adalah mahasiswa Fakultas Ilmu Komunikasi Universitas Islam Bandung dengan jumlah 368 orang. Penelitian ini pun menggunakan teknik simple random sampling dalam proses penentuan sampelnya, sehingga hasil perhitungan menentukan bahwa sampel berjumlah 79 orang. Hasil dari penelitian ini adalah efektivitas komunikasi dalam pembelajaran berbasis e-learning di Universitas Islam Bandung terbilang cukup baik, hal ini dikarenakan e-learning di Universitas Islam Bandung telah mengaplikasikan aspek Credibility, Context, Content, Clarity, Continuity and Consistency, Capability of Audience, dan Channels of Distribution dengan maksimal.